A graphene-phthalocyanine hybrid as a next photoactive layer. (August 2017) - Noh, Sung Hyun; Park, Hun; Jang, Woongsik; Koh, Ki Hwan; Yi, Minji; Lee, Ju Min; Thirumalairajan, Subramaniam; Jaung, Jae Yun; Wang, Dong Hwan; Han, Tae Hee
Abstract: Highly dispersible graphene was hybridized with a phthalocyanine derivative via covalent linkage to create a new type of donor-acceptor hybrid exhibiting photoinduced charge separation. Graphene is beneficial for the hybridization due to its easy functionalization and the unique electron accepting ability. A phthalocyanine (PC) derivative, pyrazine-based silicon phthalocyanine dichloride, possessing rich π-conjugated macrocycle was used for the electron donating purpose. The hybrid molecule showed a significant decrease in fluorescence of π-conjugated PC, implying an efficient photoinduced charge transfer occurring within the covalently-linked molecular structure consisting of "donor-acceptor". The graphene-PC hybrid molecule has also been demonstrated as an active layer material in organic photovoltaic device as well. Thus our results indeed underline the efficacy of the molecular level heterojunction of the covalently linked graphene-PC molecule in a single cell and will open new opportunities ahead for active layers research to go beyond conventional bulk-heterojunction (BHJ). Graphical abstract: